Global Games and Equilibrium Selection - Carlsson, Hans; van Damme, Eric (Econometrica, 1993)
A global game is an incomplete information game where the actual payoffstructure is determined by a rairdom draw from a given class of games and where each player makes a noisy observation of the selected game.For 2 x 2 games, it is shown that equilibrium play in a global game with vanishing noise forces the players to conform to Harsanyi and Selten's risk dominance criterion.When the uncertainty is one-dimensional, the result may be obtained by repeated elimination of dominated strategies in the global game."1'his pxper is a combinat.ion,and a subatantial generalization, of Carlxson (19R9) and Carlason and Van Damme (1989).Some basic ideas on global games and their telation to risk dominance originate from a note, written by Cadseon in 1985.The suthora thank R.einhard Selten, Lars-Gunnar Svensson, Jdrgen Weibull and various seminar audiences Cor helpful comments.The conatructive criticiam of several referees considerably improved the paper's quality.